Understanding Changes in Methodology between the 2005 and 2011 International Comparison Programs - McCarty, Paul; Vogel, Fred (World Bank, Washington, DC, 2014)
This paper provides an overview of the technical decisions that underlie the results of the 2011 international comparison program (ICP) and concludes that there are no further steps or computations that will have any substantive impact on the final results. It also provides a review of methodological changes that can affect the comparison of the 2011 results with the 2005 results. The 2005 ICP produced estimates of purchasing power parities (PPPs), real expenditures, and price level indexes for 146 countries around the world, making it the largest statistical exercise undertaken on a global basis. A number of new techniques were introduced in the 2005 ICP, and the detailed data available from that round enabled an in-depth analysis to be undertaken of not only the results but also the impact of various methods that were employed, particularly those used to link the PPPs for the six regions to provide consistent estimates for all 146 countries. This report details the choices made for ICP 2011 and how they affect comparability with ICP 2005.